Populism, Exclusion, Post-truth. Some Conceptual Caveats; Comment on "The Rise of Post-truth Populism in Pluralist Liberal Democracies: Challenges for Health Policy" - Benjamin De Cleen (Kerman University of Medical Sciences, 2018)
In their editorial, Speed and Mannion identify two main challenges "the rise of post-truth populism" poses for health policy: the populist threat to inclusive healthcare policies, and the populist threat to well-designed health policies that draw on professional expertise and research evidence. This short comment suggests some conceptual clarifications that might help in thinking through more profoundly these two important issues. It argues that we should approach right-wing populism as a combination of a populist down/up (people/elite) axis with an exclusionary nationalist in/out (member/non-member) axis. And it raises some questions regarding the equation between populism, demagogy and the rejection of expertise and scientific knowledge.